1982
DOI: 10.1139/f82-215
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Metallothionein in Rainbow Trout (Salmo gairdneri) as an Indicator of Metal Pollution in the Campbell River System

Abstract: Hepatic metallothionein was measured in livers of freshly killed rainbow trout (Salmo gairdneri) using differential pulse polarography. The fish were caught in metal-contaminated lakes of the Campbell River watershed and in a nearby control lake. The livers were analyzed for zinc, copper, and cadmium using atomic absorption spectrophotometry. High and low molecular weight protein fractions were separated by gel chromatography from liver cytosols and analyzed for metals. A downward trend from the most contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
5

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 0 publications
3
28
0
5
Order By: Relevance
“…Our data for bluegills exposed chronically to known concentrations of copper in the laboratory indicate that the quantities of copper associated with the LMW protein fraction, which contains the MTs, are related to exposure concentration and duration. Our results are similar to those obtained in fish exposed to cadmium (12,15) and to copper (20,22,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data for bluegills exposed chronically to known concentrations of copper in the laboratory indicate that the quantities of copper associated with the LMW protein fraction, which contains the MTs, are related to exposure concentration and duration. Our results are similar to those obtained in fish exposed to cadmium (12,15) and to copper (20,22,(30)(31)(32).…”
Section: Discussionsupporting
confidence: 89%
“…Fish have been exposed to mercury, zinc, and copper as well as cadmium . Experiments to determine the effect of copper exposure on MTs in fish have been perforned only on coho salmon (20)(21)(22) and rainbow trout (30)(31)(32). However, copper binding to MTs has been detected in the eel (23), flounder (9), chum salmon (10), killifish (27), skipjack (33), yellowtail (33), blackbream (33), and carp (33).…”
Section: Introductionmentioning
confidence: 99%
“…Several species of freshwater fish respond to metals by synthesizing MT. Roch et al (1982) found a good correlation between hepatic MT levels in rainbow trout caught downstream from a copper mine, and the copper level in the ambient water. Thomas et al (1985) and Kay et al (1986) report that trout, roach and stone loach all showed enhanced levels of MT in response to water-borne zinc and cadmium.…”
Section: Introductionmentioning
confidence: 76%
“…Roch, et al (1982) observent que le cadmium est toujours dominant dans les protéines è PME et è FPM . Leur importance est évidemment fonction de la concentration à la source et de la labilité du métal .…”
Section: Caractérisation Des Métalloprotéinesunclassified